PERCEPTION AMONG WOMEN ABOUT INVOLVING MEN IN FAMILY PLANNING - SANTOSH M BIRADAR; RAVI A BHOVI (International Journal of Pharma and Bio Sciences, 2013)
The family planning has always been a female domain. Gender issues, lack of awareness, misconceptions about male methods compounded by programmatic factors with excessive weightage to female methods has led to reduced utilization of male contraceptives. Objective: This study was done to know the perception of women towards male oriented contraceptives. Methodology: Field based cross-sectional study was done on the 300 married women residing in an urban slum of Bijapur. Results: couple protection rate was 65.3%. Of the 196 contraceptive users only 17(8.7%) were using condom and none of the subject's partner had undergone vasectomy. The most common reasons for non acceptance of condom were gender issues (93.6%) and inconvenience (59.7%).Vasectomy was not preferred because of gender issues (93.6%), misconceptions (52.6%) and lack of awareness (32.6%). Conclusion: Contraceptive usage among male can be increased by improving IEC activities and making suitable changes in approach of family planning services.